Fuel from waste: electrosynthesizing ammonia directly from agricultural digestate through ligand isomerization - Mendhe, Rahul Mahadeo; Mondal, Ritwik; Kottaichamy, Alagar Raja; Haridas, Akshay; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Thimmappa, Ravikumar; Thotiyl, Musthafa Ottakam (Green Chemistry, 2024)
We demonstrate that the catalytic metal centre for ammonia production can be selectively activated with only a slight alteration in ligand isomerization (alpha and beta isomers), making it practical and effective even for agricultural effluents. With almost 90% faradaic efficiency, the beta isomer generates approximately 0.64 mg h-1 cm-2 of ammonia. Energy-efficient ammonia recovery is made possible by the interfacial proton charge assembly that beta-isomerization creates, which attracts the reacting nitrate and repels the competing hydronium ions. With minimal energy consumption, this isomerization approach can interconvert agricultural effluents into ammonia fuel, reaching up to 84% of its theoretical yield and maintaining stability over 100 hours of continuous electrolysis. Ligand isomerization driven ammonia electrosynthesis from agricultural waste water.

Synergistic effects of the substrate-ligand interaction in metal-organic complexes on the de-electronation kinetics of a vitamin C fuel cell - Parmar, Muskan; Mukhopadhyay, Sanchayita; Mondal, Ritwik; Nayak, Bhojkumar; Dargily, Neethu Christudas; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Ottakam Thotiyl, Musthafa (Dalton Transactions, 2024)
The rising demand for portable energy conversion devices has spurred the advancement of direct liquid fuel cells (DLFCs) employing fuels such as alcohol, ammonia, hydrazine, and vitamin C. In these devices, various precious metal platforms have been explored to increase the de-electronation kinetics and reduce catalyst poisoning, but with substantial cost implications. We demonstrate the crucial role of ligands in non-precious organometallic complexes in influencing the de-electronation kinetics of fuel molecules through a unique substrate-ligand synergistic interaction. This unique chemistry imparts electron deficiency at the catalytic metal center while simultaneously populating the ligand with an extensive proton charge assembly. This distinct substrate-ligand interaction enhances the DLFC performance by coulombically dragging the substrate with a distinct amplification in its de-electronation kinetics. By integrating this approach with a ferricyanide/ferrocyanide half-cell reaction, a precious metal-free vitamin C fuel cell is developed, which is capable of generating an open circuit voltage of similar to 950 mV, a peak power density of similar to 97 mW cm-2 at a peak current density of similar to 215 mA cm-2 with the performance metrics nearly 1.7 times higher than a precious metal based DLFC. This highlights the potential of the substrate-ligand synergy in the design of efficient molecular catalysts for energy conversion applications. A precious metal-free biomass fuel cell through substrate-ligand interactions.